2017
DOI: 10.1371/journal.pone.0168390
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Gut Microbiome Composition and Barrier Function Are Associated with Reproductive and Metabolic Defects in Women with Polycystic Ovary Syndrome (PCOS): A Pilot Study

Abstract: BackgroundPolycystic ovary syndrome (PCOS) is a common female endocrinopathy of unclear origin characterized by hyperandrogenism, oligo-/anovulation, and ovarian cysts. Women with PCOS frequently display overweight, insulin resistance, and systemic low-grade inflammation. We hypothesized that endotoxemia resulting from a leaky gut is associated with inflammation, insulin resistance, fat accumulation, and hyperandrogenemia in PCOS. In this pilot study, we compared the stool microbiome, gut permeability, and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
261
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(277 citation statements)
references
References 47 publications
11
261
1
4
Order By: Relevance
“…Recent studies have found that the profiles of bacterial abundance exhibit similarities between the orders Clostridales and Bacteroidales . 22 , 31 , 32 Obese and non-obese women with PCOS had enriched Bacteroidetes and a decreased abundance of Akkermansia (of the phylum Verrucomicrobia ), Alistipes, Corprococcus , and Ruminococcus . 33 Akkermansia prevalence decreased in diet-induced obesity rats and was inversely correlated with peripheral inflammation in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that the profiles of bacterial abundance exhibit similarities between the orders Clostridales and Bacteroidales . 22 , 31 , 32 Obese and non-obese women with PCOS had enriched Bacteroidetes and a decreased abundance of Akkermansia (of the phylum Verrucomicrobia ), Alistipes, Corprococcus , and Ruminococcus . 33 Akkermansia prevalence decreased in diet-induced obesity rats and was inversely correlated with peripheral inflammation in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of glucose intolerance, type 2 diabetes, obesity, dyslipidemia and metabolic syndrome are increased in PCOS. [3][4][5][6][7] Alterations of gut microbiota or dysbiosis may affect various host metabolic pathways through microbiota-derived metabolites and can play a role in the development of diabetes, obesity and cardiovascular disease. However, whether this increased cardiovascular risk at young age translates into premature or higher morbidity or mortality later in life is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty‐four studies reported on 29 statistically significant biomarkers and association with altered IP . Two studies reported that fasting glucose had a weak positive correlation with IP (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Two other liver enzymes aspartate transaminase (AST) and gamma glutamyltransferase were reported to have a weak positive correlation with IP, with only AST reported as an independent risk factor for IP ( β = 0.02; 95% CI: 0.002, 0.037; P = 0.04) . One study reported that microbial diversity had a weak negative correlation with serum zonulin and stool zonulin …”
Section: Resultsmentioning
confidence: 99%